Enhanced Expression of Secreted α-Klotho in the Hippocampus Alters Nesting Behavior and Memory Formation in Mice - Li, Dongxue; Jing, Dongqing; Liu, Ziyang; Chen, Ying; Huang, Fang; Behnisch, Thomas (Frontiers in Cellular Neuroscience, 2019)
The klotho gene family consists of α-, β-, and γ-Klotho, which encode type I single-pass transmembrane proteins with large extracellular domains. α-Klotho exists as a full-length membrane-bound and as a soluble form after cleavage of the extracellular domain. Due to gene splicing, a short extracellular Klotho form can be expressed and secreted. Inactivation of α-Klotho leads to a phenotype that resembles accelerated ageing, as the expression level of the α-Klotho protein in the hippocampal formation of mice decreases with age. Here, we show that intrahippocampal viral expression of secreted human α-Klotho alters social behaviour and memory formation. Interestingly, overexpression of secreted human α-Klotho in the CA1 changed the nest-building behaviour and improved object recognition, object location and passive avoidance memory. Moreover, α-Klotho overexpression increased hippocampal synaptic transmission in response to standardized stimulation strengths, altered paired-pulse facilitation of synaptic transmission, and enhanced activity-dependent synaptic plasticity. These results indicate that memory formation benefits from an augmented level of secreted α-Klotho.